Integrins mediate their unconventional, mechanical-stress-induced secretion via RhoA and PINCH in Drosophila. - Schotman, H.; Karhinen, L.; Rabouille, C. (Journal of Cell Science, 2009)
During the epithelium remodelling such as the flattening of the Drosophila follicular epithelium, the alpha-integrin subunits are unconventionally secreted through a dGRASP-dependent route that is built de novo. The biogenetic process starts with the upregulation of a small subset of targeted mRNAs, including dgrasp. Here, we show that dgrasp mRNA upregulation is triggered by the tension of the underlying oocyte and by applied external forces at the basal side of the follicular epithelium. We show that integrins are also involved in dgrasp mRNA upregulation and the epithelium remodelling. Tension leads to the recruitment of RhoA to the plasma membrane, where it participates in its remodelling. The LIM protein PINCH can cycle to the nucleus and is involved in dgrasp mRNA upregulation. We propose that integrins are involved in triggering the biogenesis of their own unconventional secretion route that they use to strengthen adhesion and ensure epithelial integrity at the next stages of development, perhaps by acting as mechanosensors of the underlying tension through RhoA and PINCH.